2022
DOI: 10.3390/ijms232012109
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Mechanisms behind the Ultra-High Dose Rate “FLASH” Effect

Abstract: FLASH radiotherapy, or the delivery of a dose at an ultra-high dose rate (>40 Gy/s), has recently emerged as a promising tool to enhance the therapeutic index in cancer treatment. The remarkable sparing of normal tissues and equivalent tumor control by FLASH irradiation compared to conventional dose rate irradiation—the FLASH effect—has already been demonstrated in several preclinical models and even in a first patient with T-cell cutaneous lymphoma. However, the biological mechanisms responsible for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…In these experiments, the increase in the yield of micronuclei and ROS was observed not only in irradiated, but also in neighboring nonirradiated cells, the differences in the formation of micronuclei being dependent on whether the nucleus or the cytoplasm was damaged [33]. Mitochondria, being the main regulators of apoptosis and inflammation, may play an important role in the FLASH effect, in which, the degree of apoptotic and inflammatory responses significantly decreases compared with the CONV mode [34, 35]. It is likely that similar processes also occurred in our experiments during the development of eggs irradiated at a high dose rate.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, the increase in the yield of micronuclei and ROS was observed not only in irradiated, but also in neighboring nonirradiated cells, the differences in the formation of micronuclei being dependent on whether the nucleus or the cytoplasm was damaged [33]. Mitochondria, being the main regulators of apoptosis and inflammation, may play an important role in the FLASH effect, in which, the degree of apoptotic and inflammatory responses significantly decreases compared with the CONV mode [34, 35]. It is likely that similar processes also occurred in our experiments during the development of eggs irradiated at a high dose rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our research focuses on investigating the 'FLASH effect' through the simulation of oxygen consumption under the ultra-high dose rates radiation. However, certain studies have raised doubts about the validity of the oxygen depletion hypothesis in relation to the 'FLASH effect' (Bogaerts et al 2022, Lin et al 2022, Limoli and Vozenin 2023. For instance, it has been suggested that in the case of FLASH-RT, complete oxygen depletion may not occur, or that the observed protective effect of FLASH-RT is present even under normoxic conditions (air oxygen concentration).…”
Section: Discussionmentioning
confidence: 99%
“…As Liew and Mairani suggested, there is a possible issue in how to consider oxygen levels. It is true oxygen deprivation during UHDR irradiation may contribute to cell survival; however, in recent years, the oxygen depletion hypothesis has been proven debatable (Adrian et al 2022, Bogaerts et al 2022, Favaudon et al 2022, Friedl et al 2022, Lin et al 2022, Limoli and Vozenin 2023. Considering these contradictory data, before modelling the relationship between dose rate and oxygen level, a further clarification of the underlying mechanisms of the sparing effects in physical and chemical processes concerning oxygen levels is needed.…”
Section: Introductionmentioning
confidence: 99%